ANALISIS PENYALURAN KREDIT KONSUMSI PADA PERBANKAN DI INDONESIA TAHUN 2004 – 2010 - Oktavia Hartika (Jurnal Ekonomi Pembangunan, 2014)
The research objective was to determine the influence of third party fund, Non-perfoming loans (NPLs), Capital Adequacy Ratio (CAR) on consumer loans disbursed. The analytical tool used panel data regression. The sample used in this study are 7 (seven) bank based on the type of operation. Results of regression, found that variable third party fund positive and significant impact on consumer loans. Variable Non-perfoming loans (NPLs) and not significant positive effect on consumer loans. This is possible due to high NPLs in the bank's financial statements only describe the overall value of the credit. Capital Adequacy Ratio (CAR) individually have a significant negative effect on consumer loans. The study reinforces previous findings that high capital still has not been followed by increased consumer credit.